José Régio em França - Um paradigma de diálogo em sentido único - Marques, Fernando Carmino (2012)
The goal of this paper is to demonstrate the reception given to the work of José Régio in France and the debate it provoked. A staunch defender of French culture, José Régio never found in France the voice that would allow himself to establish a true dialogue with the French reader. Far from being unique, his case is a model for reflection on the availability of culture receptive influential before the perceptual difference and the originality and cultural influence that each can bring. Through the analysis of the reception of José Régio’s work in France, we will see how the much desired cultural dialogue can be interrupted by lack of culturally aware mediators.